Vertically-Aligned Carbon Nanotube Arrays on Fe3O4 Nanoparticle-Supported Silicalite-1 Monolayer - Nam Seo, Dong; Zhao, Wei; Basnet, Bijay; Pokhrel, Ashish; Jin Kim, Ik (Asian Journal of Chemistry, 2013)
Monodisperse magnetic Fe3O4 nanoparticles with the size ca. 4 nm were prepared by thermal decomposition of iron(III) acetylacetonate in organic solvent under a continuous N2 flow. These nanoparticles were spread on the silicalite-1 microcrystal-monolayer-coated silicon wafers using the simple drop-dry method as the catalysts for the synthesis of vertically-aligned carbon nanotube arrays. By a variety of characterizations, such as X-ray diffraction, scanning electron microscopy and transmission electron microscopy, the impact of catalyst size on the diameter of carbon nanotubes, were observed and discussed and so was the growth mechanism.